2007
DOI: 10.1111/j.1365-2486.2007.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2concentration, nitrogen use, and seed production in annual plants

Abstract: Elevated atmospheric CO 2 concentration ([CO 2 ]) stimulates seed mass production in many species, but the extent of stimulation shows large variation among species. We examined (1) whether seed production is enhanced more in species with lower seed nitrogen concentrations, and (2) whether seed production is enhanced by elevated [CO 2 ] when the plant uses more N for seed production. We grew 11 annuals in open top chambers that have different [CO 2 ] conditions (ambient: 370 lmol mol À1 , elevated: 700 lmol mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Regardless, the absence of strong positive seed production responses to elevated CO 2 was surprising, because many studies have found strongly positive effects of elevated CO 2 on seed production (Ackerly and Bazzaz 1995, Farnsworth and Bazzaz 1995, Huxman et al 1999, LaDeau and Clark 2001, Jablonski et al 2002, Thurig et al 2003; but see Grunzweig and Korner 2000, Ramo et al 2007). However, many of these previous studies were performed on annual plants and crop plants, both more likely to show positive responses in seed production to the addition of any limiting resource (Jablonski et al 2002, Miyagi et al 2007). Seed production is directly linked to population growth for annuals, and crop plants have been selected by humans to respond to increased resources with increased seed production (Jablonski et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless, the absence of strong positive seed production responses to elevated CO 2 was surprising, because many studies have found strongly positive effects of elevated CO 2 on seed production (Ackerly and Bazzaz 1995, Farnsworth and Bazzaz 1995, Huxman et al 1999, LaDeau and Clark 2001, Jablonski et al 2002, Thurig et al 2003; but see Grunzweig and Korner 2000, Ramo et al 2007). However, many of these previous studies were performed on annual plants and crop plants, both more likely to show positive responses in seed production to the addition of any limiting resource (Jablonski et al 2002, Miyagi et al 2007). Seed production is directly linked to population growth for annuals, and crop plants have been selected by humans to respond to increased resources with increased seed production (Jablonski et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated CO 2 has been found to 6 E-mail: jhrl@u.washington.edu strongly affect seed production of some species, but results are difficult to extrapolate to natural communities, because most studies focus on crop species (Jablonski et al 2002) or examine the response of single species to elevated CO 2 (e.g., Huxman et al 1999, LaDeau andClark 2001). To our knowledge, fewer than 10 studies have examined the reproductive responses of co-occurring plant species to elevated CO 2 in the field (Navas et al 1997, Grunzweig and Korner 2000, Thurig et al 2003, Morgan et al 2004, Stiling et al 2004, Miyagi et al 2007, Ramo et al 2007, Williams et al 2007; and only two studies have examined reproductive responses of co-occurring species to multiple global change factors in the field (Cleland et al 2006, Ramo et al 2007). Determining how global change alters seed production of co-occurring members of a plant community would lend insight into the factors that constrain seed production, and may simplify efforts to forecast population or community dynamics under global change scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, legumes exhibited a more pronounced increase in nitrogen acquisition and enhanced seed production with elevated CO 2 than non-leguminous species. Enhanced CO 2 has been reported to enhance nodulation and nitrogen fixation [36][37][38], and thus white clover may have been expected to demonstrate a seed yield increase. However, if soil nitrogen was not limiting, this may have negated any nitrogen fixation response [39].…”
Section: Seed Yield: Temperate Pasture Speciesmentioning
confidence: 99%
“…In our study, seed weight and germinability of P. annua were both significantly lower for plants grown in conditions of elevated CO 2 , and this might-at least partly-explain the differences observed in CO 2 responsiveness during the succeeding generation. Decreased germination (Farnsworth and Bazzaz 1995;Andalo et al 1996) and seed weight (Wulff and Alexander 1985) have been reported for other plant species growing in elevated CO 2 , although enhanced seed weight has also been reported (Steinger et al 2000;Miyagi et al 2007). Although most studies point to CO 2 -induced effects on seed characteristics as the mechanism through which intergenerational differences occur, it may also be possible that these effects are driven by genetic changes in a plant's response to elevated CO 2 (Ward and Kelly 2004;Lau et al 2008;Leakey et al 2009).…”
Section: Multigeneration Responsesmentioning
confidence: 96%